2012
DOI: 10.1007/s15010-012-0330-x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic obstructive pulmonary disease: an emerging comorbidity in HIV-infected patients in the HAART era?

Abstract: We evidenced a high prevalence of respiratory symptoms and COPD among HIV-infected patients. HIV infection, current cigarette smoking and previous bacterial pneumonia seem to play a significant role in the development of respiratory symptoms and COPD. Thus, our results suggest that the most at-risk HIV-infected patients should be screened for COPD to early identify those who may need specific treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
70
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(76 citation statements)
references
References 24 publications
2
70
2
2
Order By: Relevance
“…28,29 With the introduction of HAART and subsequent immunological recovery of patients, pathology as cronical obstructive pulmonary diseases (COPD), a widely spread disease in the general population, caused most significantly by smoking, 30 will increase and will probably become a new and significant comorbidity for HIV patients, especially where there is airway colonization by PCP. 31 Hence, it would be advisable to conduct early diagnosis screening of COPD in HIV patients with predisposing risk factors, 32 aimed at taking preventive measures. In a future healthcare providers should be aware of the increased likelihood of airway obstruction among HIV patients.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 With the introduction of HAART and subsequent immunological recovery of patients, pathology as cronical obstructive pulmonary diseases (COPD), a widely spread disease in the general population, caused most significantly by smoking, 30 will increase and will probably become a new and significant comorbidity for HIV patients, especially where there is airway colonization by PCP. 31 Hence, it would be advisable to conduct early diagnosis screening of COPD in HIV patients with predisposing risk factors, 32 aimed at taking preventive measures. In a future healthcare providers should be aware of the increased likelihood of airway obstruction among HIV patients.…”
Section: Discussionmentioning
confidence: 99%
“…26 An interesting recent study has shown that the prevalence of smoking may be up to three times higher in HIV-positive patients than in the general population, 27 which is an alarming finding, particularly given the high risk for morbidity in this category of patients. The risk of chronic obstructive pulmonary disease 28 and that of local infections due to a baseline suppressive lung inflammatory environment 29 have been clearly described, but the cardiac involvement is still to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 COPD is an independent risk factor for high mortality in people living with HIV, and current cigarette smoking plays a significant role in its development irrespective of HAART use. 11 Therefore, smoking cessation is crucial to reduce the high mortality rate of the population. Nevertheless, people living with HIV smoke cigarettes substantially at higher rates than the general population, that is, 40%-80% vs. 19%.…”
Section: Kim Et Almentioning
confidence: 99%